Designing multivalent NiMn-based layered nanosheets with high specific surface area and abundant active sites for solid-state hydrogen storage in magnesium hydride - Tao Zhong; Tian Xu; Liuting Zhang; Fuying Wu; Yiqun Jiang; Xuebin Yu (Journal of Magnesium and Alloys)
Catalytic doping of magnesium hydride (MgH2) to improve its hydrogen ab/desorption kinetic properties is considered to be an effective and feasible method. In solid-phase catalysis, the extent of contact between the catalyst and the substrate determines the catalytic reaction in a great sense. With large specific surface area and abundant active sites, two-dimensional (2D) nanomaterials are promising catalysts for MgH2 via providing numerous pathways for the diffusion and dissociation of hydrogen. In this regard, 2D NiMn-based layered double hydroxide and layered metallic oxide (LMO) are designed and introduced into MgH2 to improve its hydrogen storage properties. Simultaneous enhancement in interfacial contact, desorption temperature and kinetics are achieved. The MgH2+9wt% Ni3Mn-LMO composites begin to discharge hydrogen at only 190 °C and 6.10wt% H2 could be charged in 600 s at 150 °C. The activation energy for de/hydrogenation is reduced by 42.43% and 46.56%, respectively, compared to pure MgH2. Even at a low operating temperature of 235 °C, the modified system was still able to release 4.44wt% H2 in an hour, which has rarely been reported in previous studies. Microstructure observations and density functional theory calculations revealed that first, the hydrogen pumping effect of Mg2Ni/Mg2NiH4 promotes the adsorption and desorption of hydrogen molecules on the surface of MgH2, second, MnOx drew electrons from Mg2Ni, producing a new Density of State structure with a lower d-bond center. This unique change further strengthens the Mg2Ni/Mg2NiH4 pump effect on MgH2. Our work indicates that the application of 2D metal-based catalysts is a feasible and promising approach towards MgH2 for solid-state hydrogen storage to meet technical and scientific requirements.